Implications of a Culturally Evolved Self for Notions of Free Will - Robertson, Lloyd Hawkeye (Frontiers in Psychology, 2017)
Most schools in psychology have emphasized individual choice despite evidence of genetic and cultural determinism. It is suggested in this paper that the rejection of classical behaviourism by psychology and other humanities flowed from deeply held cultural assumptions about volition and free will. While compatibilists have suggested that notions of free will and determinism are not mutually exclusive, the psychological mechanisms by which such an accommodation could be explained have been inadequately explored. Drawing on research into classical cultures, this paper builds an argument that the notion of free will was adaptive flowing from culturally evolved changes to the self, and that this “evolved self,” containing assumptions of personal volition, continuity, and reason, became benchmarks of what it means to be human. The paper espouses a model of a culturally evolved self that is compatible with understandings of free will and determinism. Implications for therapeutic practice and future research are discussed.